Belajar Matematika Dengan Peta Pikiran Bagi Siswa Sekolah Menengah Pertama (SMP) - Rahma Faelasofi (Bagimu Negeri, 2018)
Currently, there is a significant effort to improve students' understanding of mathematics, one of them is by teaching students to create an interesting mind map for students, involving students in the process of understanding the material taught, and certainly not boring, because the students are actively involved in the process is an effort in helping students to understand the concept so as to be able to construct knowledge. The learning process by showing the implementation of mind map is expected to change the atmosphere of the learning process which initially tends to be mastered by educators, become more active by applying mind map. This activity is aimed in first grade of the SMP Muhammadiyah 1 Pringsewu in the academic year 2016-2017. The result of this activity is that students are able to present the material in mind map interpretation, so that students can construct knowledge creatively, according to what they understand, not just plagiarism of knowledge. So the result of the implementation of this activity is to increase the understanding of mathematical concepts, math problem-solving skills, and learning outcomes.Keywords: Mind Mapping, understanding of mathematical concepts, math problem solving, learning outcomes